2019
DOI: 10.3389/fcimb.2019.00272
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Dormant “Non-culturable” Mycobacterium tuberculosis Is Characterized by Immediate Transcriptional Burst

Abstract: Under unfavorable conditions such as host immune responses and environmental stresses, human pathogen Mycobacterium tuberculosis may acquire the dormancy phenotype characterized by “non-culturability” and a substantial decrease of metabolic activity and global transcription rates. Here, we found that the transition of M. tuberculosis from the dormant “non-culturable” (NC) cells to fully replicating population in vitro occurred not earlier tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Under these conditions, the bacterium underwent growth arrest and a decrease in respiration rate. Salina et al (2014Salina et al ( , 2019 have studied growth in potassium-deficient media which generates non-culturable (NC) bacilli, tolerant to cell wall targeting antimicrobials. Potassium supplementation enables resuscitation of growth.…”
Section: In Vitro Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, the bacterium underwent growth arrest and a decrease in respiration rate. Salina et al (2014Salina et al ( , 2019 have studied growth in potassium-deficient media which generates non-culturable (NC) bacilli, tolerant to cell wall targeting antimicrobials. Potassium supplementation enables resuscitation of growth.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…TCS components mprAB, kdpD, prrA; whiB1, whiB6; kstR (involved in cholesterol degradation pathway); icl1, mutA (methylmalonyl pathway). bkdA, bkdB, bkdC, fadE2, fadE13, accD2 (implicated in the catabolism of branched-chain keto and amino acids); Proteases and peptidases: pepD, pepR, htrA and clpC2; arcA (arginine deiminase); gcvB (glycine dehydrogenase), which are involved in degradation of arginine and glycine, respectively; hsaG (involved in the degradation of aromatic compounds); nuoA-N; sigA, sigB, sigE, sigF, sigG, sigH, sigI, sigL, and sigM Salina et al, 2014Salina et al, , 2019 2019) and whiB6 was upregulated during potassium depletion (Salina et al, 2014(Salina et al, , 2019. Analysis of the transcriptional regulatory network that underlies the response to vitamin C, showed an early response (upto 1 h), an intermediate response (between 2 and 8 h) and a late response (24 h).…”
Section: Aguilar-ayala Et Al 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of MTS1338 dramatically changes the bacterial growth rate (Arnvig et al, 2011; Ignatov et al, 2015). Our experiments with M. tuberculosis dormancy and resuscitation in vitro demonstrated that MTS1338 participates in entering dormancy (Ignatov et al, 2015), but is not involved in the resuscitation process (Salina et al, 2019). In vivo , high levels of MTS1338 transcription were reported for M. tuberculosis residing in chronically infected mouse lungs (Arnvig et al, 2011; Ignatov et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeting M.tb populations resuscitating from dormancy would also be critical in the development of therapeutic vaccines, as to eliminate/minimize reactivation. Mycobacterial resuscitation is a complex process and is regulated in a coordinated transcriptional burst preceding expression of metabolic and growth-related pathways ( 92 ). Resuscitation promoting factors (RPFs) represent a major class of antigens involved in this process and may represent promising vaccine antigen targets ( 92 94 ).…”
Section: Advancing Therapeutic Tb Vaccine Designmentioning
confidence: 99%